Land lease markets and agricultural efficiency: theory and evidence from Ethiopia - Pender, John L.; Fafchamps, Marcel (International Food Policy Research Institute, 2001)
This paper develops a theoretical model of land leasing that includes transaction costs of enforcing labor effort, risk pooling motives and non-tradable productive inputs. We test the implications of this model compared to those of the “Marshallian” (unenforceable labor effort) and “New School” (costlessly enforceable effort) perspectives using data collected from four villages in Ethiopia. We find that land lease markets operate relatively efficiently in the villages studied, supporting the New School perspective relative to the other two models. Land contract choice is found to depend upon the social relationships between landlords and tenants, but differences in contracts are not associated with significant differences in input use or output value per hectare. We find that other household and village characteristics do affect input use and output value, suggesting imperfections in other factor markets. These results imply that interventions to improve the functioning of land lease markets are likely to be of little benefit for agricultural efficiency in the villages studied, whereas improvements in other factor markets may be more beneficial.